The muleteers of the central highlands during the 19th century - Manrique, Nelson (1983)
The muleteer played a transcendental role in the organization of the regional economy of the central highlands throughout the 19th century. In fact, this activity constituted the backbone of the development of the mercantile economy in the region in the three centuries prior to the construction of the Central Railway, which was completed at the beginning of the 20th century, and even continued to play a significant role after that it came into operation, based on a radical redefinition of traditional circuits, until a relatively recent period. The notes that follow are intended to provide a very general view of the nature and characteristics of this activity, its impact on the organization of the regional economy and the universe of social relations that were interwoven around the muleteers and the muleteer.